(untitled) (UMRAN - Journal of Islamic and Civilizational Studies, 2026)
Nuzriah, described in Singapore Muslim estate-planning discourse as a form of Nadhar or Nazar, is discussed as a mechanism for transferring property to selected beneficiaries shortly before death. Its development in Singapore is closely linked to MUIS Fatwa and Irsyad materials, joint-tenancy concerns, family hardship and the need for contemporary ijtihād in Muslim estate planning. This article examines whether Nuzriah can be reconciled with Muslim-law principles and the Administration of Muslim Law Act 1966 (AMLA). It seeks to identify the doctrinal and legal nature of Nuzriah within the framework of Hibah, Waṣiyyah, Nadhar and Faraid; analyse the decision in Mohamed Ismail bin Ibrahim and Another v Mohammad Taha bin Ibrahim [2004] SGHC 210; and evaluate how Nuzriah may be refined and regulated as a contemporary Muslim estate-planning instrument. Adopting a doctrinal legal research method, the study analyses AMLA, reported judgments, MUIS-related Fatwa and Irsyad materials, and classical and contemporary maslahah writings through statutory interpretation, case analysis and doctrinal comparison with the Shāfiʿī position and wider Muslim-law principles. The findings indicate that Nuzriah reflects a genuine maslahah-based response to practical estate-planning difficulties, especially involving jointly owned property and family dependants. However, where its legal effect is tied to a period immediately before death, it must be carefully reconciled with the safeguards of Hibah, Waṣiyyah, Nadhar, Faraid and AMLA. The article argues that Mohamed Ismail should not be understood as a general rejection of MUIS’s religious authority. Rather, it should be read as a judicial reminder that the legal substance and enforceability of a Nuzriah instrument remain subject to scrutiny, particularly where proprietary rights and heirs’ entitlements are disputed. It concludes that Nuzriah, if retained as an estate-planning mechanism, should be supported by clearer doctrinal foundations, careful drafting, public education, and appropriate statutory or administrative safeguards.